Memaknai Kisah Daud dan Batsyeba Melalui Kritik Naratif Dalam Teks 2 Samuel 11:1-27 - Yola Pradita (Institut Agama Kristen Negeri Palangka Raya, 2021)
David was a clever king, great at war, correct in making decisions, sincere and loyal. However, the writer book of 2 Samuel did not consider King David to be a great dan perpect king in his leadership. David had a week point too, so that David’s sin was told frankly. This study aims to interpret David weakness in the story of David and Bathsheba (2 Samuel 11: 1-27) through the method of narrative criticism, then it can be provide relevance for today's life. The result of the narrative criticism that has been done is David disregarded God's law in using his power, even he was sleeping with Bathsheba, the Uriah wife’s. Bathsheba and the other characters in the narrative are only supporting figures representing small people to criticize David's power. The results of this interpretation can be relevant for Christian leaders today. This text means that everything we are doing must be in accordance with God's perspective. A Christian leader in his power must be under God's law, because a leader is an example and role model for many people. Daud adalah seorang raja yang pandai, hebat dalam peperangan, tepat dalam mengambil keputusan, tulus dan setia. Namun, penulis kitab 2 Samuel tidak menganggap raja Daud sebagai raja yang hebat dan sempurna dalam kepemimpinannya. Daud juga mempunyai titik kelemahan sehingga dosa Daud pun diceritakan dengan terus terang. Penelitian ini bertujuan untuk memaknai kelemahan Daud dalam kisah Daud dan Batsyeba (2 Samuel 11:1-27) melalui metode kritik naratif, kemudian direlevansikan bagi kehidupan masa kini. Hasil dari kritik naratif yang sudah dilakukan adalah Daud tidak menghiraukan hukum Allah dalam menggunakan kekuasaannya, ia tidur dengan Batsyeba, istri Uria. Batsyeba dan tokoh lain dalam narasi hanyalah tokoh pendukung yang mewakili orang-orang kecil untuk mengkritik kekuasaan Daud. Hasil penafsiran ini dapat direlevansikan bagi para pemimpin Kristen masa kini. Teks ini bermakna bahwa segala sesuatu yang dilakukan harus sesuai dengan perspektif Allah. Seorang pemimpin kristen dalam kekuasaannya harus berada di bawah hukum Allah, sebab seorang pemimpin adalah teladan dan panutan bagi banyak orang.